Compulsive Internet Use Scale for assessment of self-reported problematic internet use in primary school-aged children - Jusienė, Roma; Pakalniškienė, Vilmantė; Wu, Jennifer Chun-Li; Sebre, Sandra B. (Frontiers in Psychiatry, 2023)
The tremendous growth of internet use during past few decades has been primarily led by young people. Despite a plenitude of studies reporting the pros and cons of excessive internet use by adolescents, the internet use of primary school-aged children is under-researched. First, there is lack of reliable and valid cultural invariant self-report instruments for children younger than 11-years-old. Secondly, there is no consensus on whether primary school-aged children can reliably report on their internet use. This study aimed to examine the psychometric properties of the Compulsive Internet Use Scale (CIUS) as reported by primary school-aged children in three different countries/regions. Paper-pencil format CIUS questionnaires were completed by a total of 691 children aged 8 to 10 years old, 236 of them Latvian, 207 Lithuanian, and 248 Taiwanese, as well as by one of their parents, at two-time points, separated by a one-year interval. The parents also reported on the child’s emotional and behavioral difficulties. Confirmatory factor analysis indicated that for the child self-report, a 10-item CIUS showed the best fit and good psychometric properties: solid structural validity; very good internal consistency; appropriate stability and predictive validity after one year; as well as sound sensitivity and specificity when compared to the 14-item CIUS parent-report form. Child self-report CIUS ratings correlated with time online reported by the child and parent and with emotional and behavioral problems reported by the parent. This study indicates that children as young as 8-10 years old can reliably and consistently provide valuable information on their problematic use of the internet.